2005
DOI: 10.1111/j.1365-2621.2005.tb11500.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Affects Physicochemical and Conformational Changes of Threadfin Bream Myosin and Actin in a Setting Model

Abstract: A ATDIGUL TDIGUL TDIGUL TDIGUL TDIGUL ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: : : : : The effect of C The effect of C The effect of C The effect of C The effect of Ca a a a a 2+ 2+ 2+ 2+ 2+ on physicochemical and confor on physicochemical and confor on physicochemical and confor on physicochemical and confor on physicochemical and conformational changes of thr mational changes of thr mational changes of thr mational changes of thr mational changes of threadfin br eadfin br eadfin br eadfin br eadfin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Shear stress of Pacific whiting surimi also increased when 0.2 g CaCl 2 /100 g was added, while lower concentrations (0.05-0.1 g/100 g) were found to be effective in Alaska pollock (Lee and Park, 1998). Besides being a TGase activator, Ca 2þ has been reported to promote hydrophobic interactions and disulfide linkages during setting of fish myosin and actomyosin by inducing the exposure of hydrophobic residues and sulfhydryl groups of the protein molecule (Hemung & Yongsawatdigul, 2005;Yongsawatdigul & Sinsuwan, 2007). Thus, addition of CaCl 2 to lizardfish surimi in the presence of TBSP could enhance hydrophobic interactions and disulfide linkages among molecules, resulting in an increase in breaking force and deformation value.…”
Section: Effect Of Tbsp On Textural Properties Of Lizardfish Surimi Gelsmentioning
confidence: 90%
“…Shear stress of Pacific whiting surimi also increased when 0.2 g CaCl 2 /100 g was added, while lower concentrations (0.05-0.1 g/100 g) were found to be effective in Alaska pollock (Lee and Park, 1998). Besides being a TGase activator, Ca 2þ has been reported to promote hydrophobic interactions and disulfide linkages during setting of fish myosin and actomyosin by inducing the exposure of hydrophobic residues and sulfhydryl groups of the protein molecule (Hemung & Yongsawatdigul, 2005;Yongsawatdigul & Sinsuwan, 2007). Thus, addition of CaCl 2 to lizardfish surimi in the presence of TBSP could enhance hydrophobic interactions and disulfide linkages among molecules, resulting in an increase in breaking force and deformation value.…”
Section: Effect Of Tbsp On Textural Properties Of Lizardfish Surimi Gelsmentioning
confidence: 90%
“…This confirmed that endogenous TGase, which is a Ca 2+ -dependent enzyme and known to mainly improve breaking force value, could be partly responsible for gel improvement of SC mince, especially at 40 • C. However, an increase in breaking force observed at other heating regimes was unlikely to be caused by TGase-catalyzed reaction, as the condition at 25, 65, and 90 • C is not optimal for TGase activity. It has been reported that Ca 2+ contributed to an increase in hydrophobic interactions and the formation of disulfide linkages of threadfin bream myosin and tilapia actomyosin at 10-100 mM equivalent to 0.1-1.0% (Hemung and Yongsawatdigul, 2005;Yongsawatdigul and Sinsuwan, 2007). Enhancement of such interactions could in part contribute to the positive effect of Ca 2+ on breaking force of SC and CC mince gels at heating regimes other than 40 • C.…”
Section: Effect Of Cacl 2 On Gel-forming Abilitymentioning
confidence: 91%
“…The gel-suppressing effect of Ca 2+ on carp surimi could be due to extensive conformational changes of myosin induced by Ca 2+ . α-Helical content of threadfin bream myosin drastically decreased as Ca 2+ concentration increased from 10 to 100 mM (Hemung and Yongsawatdigul, 2005). In addition, high concentrations of Ca 2+ at 200 mM also perturbed globular head of myosin, decreasing Ca 2+ -ATPase activity (Hemung and Yongsawatdigul, 2005).…”
Section: Effect Of Cacl 2 On Gel-forming Abilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Apart from ε-(γ -glutamyl) lysine isopeptide bonds catalyzed by Ca 2+ -dependent endogenous TGase, hydrophobic interactions and disulphide linkages could be involved during setting of fish protein. 98 Benjakul and Visessanguan 92 found that the addition of CaCl 2 in the sol of surimi from both species of bigeye snapper (P. tayenus and P. macracanthus) prior to setting either at 25 or 40 • C, followed by heating at 90 • C, resulted in an increase in both breaking force and deformation of surimi from both species. The increase was more pronounced with increasing calcium chloride levels (0-100 mmol kg −1 ).…”
Section: Endogenous Tgasementioning
confidence: 99%